2016
DOI: 10.1016/j.jvs.2014.06.110
|View full text |Cite
|
Sign up to set email alerts
|

Adipose phenotype predicts early human autogenous arteriovenous hemodialysis remodeling

Abstract: Objective Substantial proportions of autogenous arteriovenous hemodialysis access fistulas (AVF) fail to mature for unclear reasons. AVFs develop in a large mass of surrounding adipose tissue that is increasingly recognized as an active participant in the vascular response to injury via paracrine and endocrine mechanisms. We thus hypothesized that baseline phenotypic characteristics of the adipose juxtaposed to the developing AVF associate with subsequent inward or outward vein wall remodeling. Methods Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…PVAT harbors numerous amounts of inflammatory cells. Damage to PVAT results in an inflammatory response driven by adipocyte-derived factors such as resistin, leptin, or the cytokines IL-6, TNF-α, and CCL2 ( 154 ). Protective effects of adiponectin on NADPH oxidase, superoxide production and NO bioavailability in the vessel wall are reduced after PVAT damage ( 155 ).…”
Section: Perivascular Adipose Tissue (Pvat)mentioning
confidence: 99%
“…PVAT harbors numerous amounts of inflammatory cells. Damage to PVAT results in an inflammatory response driven by adipocyte-derived factors such as resistin, leptin, or the cytokines IL-6, TNF-α, and CCL2 ( 154 ). Protective effects of adiponectin on NADPH oxidase, superoxide production and NO bioavailability in the vessel wall are reduced after PVAT damage ( 155 ).…”
Section: Perivascular Adipose Tissue (Pvat)mentioning
confidence: 99%
“…We reported that levels of local adipose-associated mediators correlated with markers of vein remodeling at a single time point 4 to 6 weeks after access surgery. 25 Here we expanded on that work by evaluating vascular wall adaptations at several time points, which extended from placement to first cannulation, and in a larger, more diverse, and better-described patient population.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 24 Recently, we demonstrated in a small prospective study that levels of adipose interleukin (IL)-8, tumor necrosis factor-α, monocyte chemoattractant protein (MCP)-1, resistin, and adiponectin were inversely correlated with venous diameter change, and MCP-1 and adiponectin were inversely correlated with flow volume in human AVF at 4 to 6 weeks after access creation. 25 …”
mentioning
confidence: 99%
“…42 We also recently demonstrated that local adipose adiponectin was inversely correlated with eventual flow volume (a marker of arteriovenous fistula maturation) in the early stages following hemodialysis access creation surgery. 43 Investigators studying circulating plasma adipocytokine levels found a nearly significant trend toward elevated preoperative leptin in patients who developed SSI. 17, 18 A similar correlation between circulating adiponectin and wound infection was not found.…”
Section: Discussionmentioning
confidence: 99%